2010
DOI: 10.1016/j.archoralbio.2010.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Adherence in vitro of Candida albicans to plasma treated acrylic resin. Effect of plasma parameters, surface roughness and salivary pellicle

Abstract: Results demonstrated that ArO2/70W and ArSF6/70W plasma treatments showed promising potential for reducing the adherence of C. albicans to denture base resins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
110
1
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(123 citation statements)
references
References 47 publications
6
110
1
6
Order By: Relevance
“…Nurhaerani et al found that CF4 plasma was useful in inhibiting Streptococcus mutans adhesion on stainless steel surface 22) . Zamperini et al confirmed that ArO2/70W and ArSF6/70W plasma treatment groups showed significantly reduced Candida albicans biofilm adhesion than the control group after plasma treatment of heat-curing acrylic resin samples 23) . However, the early adherence of Candida albicans on plasma-treated, heat-polymerized acrylic resins is rarely investigated.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Nurhaerani et al found that CF4 plasma was useful in inhibiting Streptococcus mutans adhesion on stainless steel surface 22) . Zamperini et al confirmed that ArO2/70W and ArSF6/70W plasma treatment groups showed significantly reduced Candida albicans biofilm adhesion than the control group after plasma treatment of heat-curing acrylic resin samples 23) . However, the early adherence of Candida albicans on plasma-treated, heat-polymerized acrylic resins is rarely investigated.…”
Section: Introductionmentioning
confidence: 78%
“…In the present study, saliva was used to better simulate Candida albicans adherence. Recent reports stated that salivary films neither influenced Candida albicans adhesion nor significantly altered surface free energy and its polar and dispersive components 23,24) . In this study, Ar/O2 plasma treatment caused a significant decrease in contact angle and Candida albicans adhesion (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although some studies have suggested that the adhesion ability of yeasts to polymeric surfaces is modulated by hydrophobic forces, others found no correlation between hydrophobicity and Candida adhesion (8)(9)(10). It has also been reported that an increase in surface roughness enhances C. albicans retention (11)(12)(13)(14) as it increases the surface area and/or shear forces (5), thus allowing easier microbial attachment and difficult detachment even when the prosthesis has been cleaned with antimicrobial agents (10). However, most of these studies focused on the adherence of C. albicans to rough denture surfaces (3,(11)(12)(13), but failed to investigate the efficiency of antimicrobial agents in removing yeasts from these surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Candida albicans, which has the ability to adhere and proliferate on both soft and hard tissues (2), has been widely associated with the etiology of denture stomatitis (3,4). Since adherence of C. albicans to polymethyl methacrylate (PMMA) resin surfaces is an essential and necessary step for successful colonization and development of pathogenesis, (3) treatment of denture stomatitis should target reduction of initial fungal adherence (5).…”
Section: Introductionmentioning
confidence: 99%